2013
DOI: 10.1016/j.kjms.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin's lymphoma‐related vanishing bile duct syndrome: A case report and literature review

Abstract: We report the case of a 38-year-old man who developed vanishing bile duct syndrome in association with Hodgkin's lymphoma. He was noted to have cervical lymphadenopathy and marked elevation of total serum bilirubin at diagnosis. He achieved complete remission with normalization of serum bilirubin after eight courses of Adriamycin, bleomycin, vinblastine, and dacarbazine chemotherapy followed with autologous hematopoietic cell transplantation. Consecutive liver biopsies performed at diagnosis and at the stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 18 publications
(27 reference statements)
1
28
0
Order By: Relevance
“…[38]1YesFullNoCureUmit H. [39]1UnknownUnknownUnknownUnknownGill R.M. [40]1YesReducedNoHepatic failureForamiti S. [41]1YesFullYesHepatic failureGagnon MF [42]1YesFullNoCureWong KM [43]1YesFullNoCureAleem A1 [44]1YesFullNoHepatic failureNader K [45]1YesFullNoHepatic failureOur patient1YesFullYesCure*either chemotherapy or radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…[38]1YesFullNoCureUmit H. [39]1UnknownUnknownUnknownUnknownGill R.M. [40]1YesReducedNoHepatic failureForamiti S. [41]1YesFullYesHepatic failureGagnon MF [42]1YesFullNoCureWong KM [43]1YesFullNoCureAleem A1 [44]1YesFullNoHepatic failureNader K [45]1YesFullNoHepatic failureOur patient1YesFullYesCure*either chemotherapy or radiotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Not only lymphoma responded to 8 cycles of ABVD regimen followed by autologous hematopoietic stem cell transplantation, but also VBDS disappeared. The repeated liver biopsy at the moment of lymphoma complete remission found interlobular bile ducts regeneration, an argument for the reversibility of bile duct injury in VBDS [58]. Such isolated cases do not allow us to draw any definite conclusion on the general reversibility of VBDS.…”
Section: Hodgkin's Lymphoma and Vanishing Bile Duct Syndromementioning
confidence: 92%
“…30 A second theory includes direct bile duct damage by paraneoplastic toxic cytokines released by the lymphoma cells. 31 Without treatment, the natural progression is hepatic failure. In cases of VBDS that are not related to HL, the bile ducts disappear irreversibly; however, as a paraneoplastic phenomenon, full resolution of symptomatology, laboratory, and histologic findings has been described with appropriate HL therapy in some case reports.…”
Section: Idiopathic Cholestasismentioning
confidence: 99%
“…In cases of VBDS that are not related to HL, the bile ducts disappear irreversibly; however, as a paraneoplastic phenomenon, full resolution of symptomatology, laboratory, and histologic findings has been described with appropriate HL therapy in some case reports. 5,30,31 Two reviews of HL and VBDS in both adults and children reported severe complications, notably liver failure and sepsis, and high mortality rates. The addition of steroid therapy to standard chemotherapy and radiotherapy improved hepatic function and was more likely to lead to complete remission.…”
Section: Idiopathic Cholestasismentioning
confidence: 99%